OPTICAL COHERENCE TOMOGRAPHIC CHARACTERISTICS OF IDIOPATHIC CHOROIDAL NEOVASCULARISATION AND STAGING - Shah, Syed Nasir Ali; Kang, Qian Yan; Ma, Bo; Gao, Shan; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2015)
Background: Idiopathic choroidal neovascularisation (ICNV) is the development of choroidal neovascularisation (CNV) in young adults without any apparent manifestations of primary ocular or systemic diseases We aim to assess characteristics and pathological changes at various stages in ICNV by optical coherence tomography(OCT). Methods: We reviewed clinical charts of 40 ICNV eyes and classified them into three stages. Active stage <1 month, intermediate 1-3 months and cicatricial >3 months period after initiation of treatment in naïve ICNV eyes. OCT characteristics of these morphological changes were determined. Parameters such as mean volume (MV), central macular thickness (CMT) and neovessels size (thickness and diameter) were analyzed and compared using one -way ANOVA. Results: We have 12 males and 28 females with a mean age of 30.1±7.80 years. In active stage, heterogenous activity of CNV was observed, along with disrupted RPE layer, surrounded by subretinal fluids and loss of foveal depression. In intermediate stage, CNV reflection appears homogenous with smooth peripheral Retinal pigment epithelium (RPE) lesion and reduction in retinal thickness. In cicatricial stage, OCT presents dome shaped elevation, strong homogenous reflection, absence of subretinal fluids and reformation of foveal depression. We have found that difference in mean volume and choroidal neovessels thickness was statistically significant in the three stages. Conclusions: In our study we have concluded that OCT is useful tool for following the clinical course of ICNV and understanding the pathological changes in CNV regression.